MANAGMENT OF CANINE TRANSMISSIBLE VENEREAL TUMOR, RETROSPECTIVE STUDY OF FIVE CASES - Dameski, Pance; Karabolovski, Nikola; Dodovski, Petar; Ristevski, Mimi; Avramov, Aleksandar; Zdraveski, Igor; Pejchinovska, Natasha; Hristovska, Talija (Horizons - International Scientific Journal, 2018)
Tumors are the most common fatal disorders observed in animals. Nearly 16 to 24% of dogs deaths are associated with tumors. For many years, the surgical excision of tumors in animals was the only treatment technique. Canine transmissible venereal tumor (TVT), also known as transmissible venereal sarcoma and Stricker's sarcoma, is a naturally occurring, horizontally transmitted infectious histiocytic tumor of dogs usually spread by coitus, but it may also be spread by licking, biting and sniffing tumoraffected areas. It has been observed occasionally in other canids, such as foxes, coyotes and jackals. It has also been known as infectious sarcoma, venereal granuloma, canine condyloma, transmissible sarcoma and transmissible lymphosarcoma. One of the goal of this study was to examinethe method of treatment that is most effective.